The Yazidi Genocide: Between Legal Text and Judicial Implementation: A Study of the Iraqi and International Experience - Jumaah, Mohammed; Nouri, Yassir (Journal of Legal Sciences, 2026)
The Yazidi minority in Iraq suffered one of the gravest crimes in modern history, through by the attack launched by armed terrorist groups in 2014, during which acts amounting to the crime of genocide were committed according to the 1948 Genocide Convention. These crimes included systematic killing, enslavement, forced displacement, and sexual violence, particularly against women and children. This study examines the international legal framework for the crime of genocide and its elements, analyzing its applicability to the crimes committed against the Yazidis and highlighting the challenges of proving the Mens Rea and "special intent" on the part of the perpetrators. The study also reviews judicial practices at the national and international levels, including trials in Iraq, which were often conducted under terrorism charges, compared to trials in some European countries that explicitly described the acts as "genocide." The research aims to assess the gap between legal text and practical application, and to propose solutions to strengthen international criminal justice and ensure that perpetrators of these crimes do not escape punishment.